SUSCEPTIBILITY TO SPONTANEOUS COMBUSTION OF SOME INDONESIAN COALS - DATIN FATIA UMAR; BINARKO SANTOSO; BUKIN DAULAY (Indonesian Mining Journal, 2012)
Eight Indonesian coal samples of different moisture contents obtained from the various coalfi elds were used to study spontaneous combustion characteristics by differential thermal analysis (DTA) and crossing point temperature (CPT). Results indicate that there is no direct correlation between the spontaneous combustion test data and the individual properties of the coal samples by both DTA and CPT test methods; in this study, a preliminary conclusion can be drawn on the coal moisture content effect on spontaneous combustion. Higher moisture content coals are more susceptible to spontaneous combustion than that of lower moisture content coals. It also can be stated that the susceptibility of coal to spontaneous combustion is basically a complex. Clearly more tests are required to investigate the effect of coal properties in more detail from other Indonesian coals that have various types and ranks.